Nutrient and Energy Recovery from anaerobic digester (AD) centrate using an algal system - Selvaratnam, T.; Kharel, H.L.; Tan, M. (University of Jaffna, 2022)
Anaerobic digestion (AD) systems yield methane from wet sludge/biomass leaving carbon-depleted wastewater known as centrate in municipal wastewater treatment plants. Centrate is an ideal feedstock for nutrient/energy recovery because it is highly concentrated and is thus low volume. High nutrient levels are found in centrate in the form of ammonium and phosphate ions. This current study focused on the potential of using centrate to recover nutrients and energy through an algal-based system. A red-algal (Galdieria sulphuraria) strain was used for this application for the treatment of centrate from municipal AD systems.
Keywords: Bioremediation; Microalgae; Galdieria sulphuraria; Nutrient recovery